HAK DAN KEDUDUKAN PEREMPUAN DALAM HUKUM KELUARGA (Studi Atas Pemikiran Feminisme Amina Wadud) - Fahmi Assulthoni; Farida Yuniati; Nuri Herachwati (LP2M IAI Miftahul Ulum Pamekasan, 2022)
Amina Wadud as a feminist activist is considered to widen the context of gender equality for women on the one hand. But on the other hand, she is labelled as having made a